Privacidad, difusión de información personal y auto-imagen [e imagen de sí mismos] de los adolescentes espaníƒoles en las redes sociales. El caso de Fotolog (Communication & Society, 2013)
This paper presents the results of a research study that analyzes the quantitative content of 355 entries on the social network Fotolog to determine the type of information shared by adolescents on the Web 2.0. The variables considered are related to intensity of use of the platform, the personal information disclosed, and the representational strategies used. The study concludes that Spanish adolescents strategically manage personal information and privacy. Adolescents sacrifice part of their privacy in exchange for the popularity and prestige they obtain as a result of being recognized by others in their idealized identity of themselves that they present.